The Effectiveness of Selective Serotonin Reuptake Inhibitors for Treatment of Obsessive-Compulsive Disorder in Adolescents and Children: A Systematic Review and Meta-Analysis - Kotapati, Vijaya Padma; Khan, Ali M.; Dar, Sara; Begum, Gulshan; Bachu, Ramya; Adnan, Mahwish; Zubair, Aarij; Ahmed, Rizwan A. (Frontiers in Psychiatry, 2019)
Background: Obsessive-compulsive disorder (OCD) is a common behavioral disorder among adolescents and children. The selective serotonin reuptake inhibitors (SSRIs) are the first pharmacological choice for this condition due to mild adverse effect profile. Objective: This systematic review was performed to evaluate the efficacy of SSRI for OCD in adolescents and children. Methods: Search terms were entered into PubMed, PsycINFO, Scopus, CINAHL, and Google Scholar. The included studies were randomized, placebo-controlled trials of SSRIs conducted in populations of children and adolescents younger than 18 years. Change from baseline Children’s Yale-Brown Obsessive-Compulsive Scale (CY-BOCS), end-treatment CY-BOCS with respective SD, and response and remission rates were collected for continuous and dichotomous outcome assessment, respectively. Cochrane Rev Man software was used for meta-analyses, providing Forest plots where applicable. Results: SSRIs were superior to placebo with a small effect size. There was no additional benefit of combination treatment over cognitive behavioral therapy (CBT) alone, but CBT added substantial benefit to SSRI monotherapy. Fluoxetine and sertraline appear to be superior to fluvoxamine. Conclusion: The results of current systematic review and meta-analysis support the existing National Institute for Health and Care Excellence (NICE) guidelines for choosing CBT as first line of treatment and substituting it with SSRI, depending on patient preference. Adding CBT to current SSRI treatment is effective for non-responders and partial responders, but adding SSRI to ongoing CBT does not prove beneficial. The SSRIs have different effectiveness, and their relative efficacy remains to be investigated.